MPMR: Multi-Scale Feature and Probability Map for Melanoma Recognition - Zhang, Dong; Han, Hongcheng; Du, Shaoyi; Zhu, Longfei; Yang, Jing; Wang, Xijing; Wang, Lin; Xu, Meifeng (Frontiers in Medicine, 2022)
Malignant melanoma (MM) recognition in whole-slide images (WSIs) is challenging for the huge image size of billions of pixels and complex visual characteristics. We propose a novel automatic melanoma recognition method based on the multi-scale features and probability map, named MPMR. First, we introduce the idea of breaking up the WSI into patches to overcome the difficult-to-calculate problem of WSIs with huge sizes. Second, to obtain and visualize the recognition result of MM tissues in WSIs, a probability mapping method is proposed to generate the mask based on predicted categories, confidence probabilities, and location information of patches. Third, considering that the pathological features related to melanoma are at different scales such as tissue, cell, and nucleus, to enhance the representation of multi-scale features is important for melanoma recognition, we construct a multi-scale feature fusion architecture by the additional branch paths and shortcut connections, which extracts the enriched lesion features from low-level features containing more detail information and high-level features containing more semantic information. Fourth, to improve the extraction feature of the irregular-shaped lesion and focus on essential features, we reconstructed the residual blocks by deformable convolution and channel attention mechanism, which further reduces information redundancy and noisy features. The experimental results demonstrate that the proposed method outperforms the compared algorithms, and it has a potential for practical applications in clinical diagnosis.